Study of Bell Correlations From Local Un-entangled States of Light and Quantum Electro-dynamics - Sica, Louis (New Trends in Physical Science Research Vol. 3, 2022)
It has long been assumed that a theoretical computation of the Bell correlation necessitates the explicit use of an entangled state, based on the Bell theorem. In the down-converter sources utilized in Bell experiments, such a physical superposition of light waves occurs. Wave propagation to spatially distant detectors, on the other hand, eliminates this physical superposition. Local waves and the source boundary conditions of their previously entangled state must thus produce Bell correlations. Bell correlations are estimated in the present model using disentangled separated waves, nonlinear optics boundary conditions, and quantum electrodynamics features of single-photon and vacuum states. Based on the fact that the possibility of interference was found to be necessary by the designers of Bell-experiment sources, transient interference between photon-excited waves and photon-empty waves is assumed. Local random variables are used in this paradigm, but no underlying causality is specified. The current paper provides a calculation of the Bell correlation that begins with the principle that physically separated, non-superimposed, electromagnetic waves do not instantaneously influence each other.